Preventive dental care is associated with improved healthcare outcomes and reduced costs for Medicaid members with diabetes - Lamster, Ira B.; Malloy, Kevin P.; DiMura, Philip M.; Cheng, Bin; Wagner, Victoria L.; Matson, Jacqueline M.; Proj, Anisa; Xi, Yizhao; Abel, Stephen N.; Alfano, Michael C. (Frontiers in Dental Medicine, 2022)
Introduction: Preventive dental services have been associated with improved health outcomes. This study expands on previous observations by examining the relationship between oral health care and health care outcomes and costs in a publicly insured population with diabetes. Methods: Utilization of dental services, health care outcomes and costs were evaluated for New York State Medicaid members with a diagnosis of diabetes mellitus (DM), ages 42 to 64, who were continuously enrolled between July 1, 2012 and June 30, 2015. Utilization of dental services focused on preventive dental care (PDC), and extractions and endodontic treatment (both indicative of advanced dental infection). Data were analyzed using regression models with propensity score weighting to control for potential confounding. Results: Receipt of PDC was associated with lower utilization rates and costs compared to members who did not access dental services. The most pronounced average cost difference was observed for inpatient admissions at $823 per year for members who had at least one PDC without extraction or endodontic treatment. Each additional PDC visit received was associated with an 11% lower rate of inpatient admissions and lower average inpatient costs by $407 per member. The need for a dental extraction or endodontic therapy was associated with relatively higher rates and costs. Conclusions: These findings demonstrate an association between PDC and improved health care outcome rates and lower average costs among members with DM and suggest a general health benefit associated with provision of preventive dental care for persons with DM.